2017
DOI: 10.3390/ijms19010039
|View full text |Cite
|
Sign up to set email alerts
|

BMP Signalling at the Crossroad of Liver Fibrosis and Regeneration

Abstract: Bone Morphogenetic Proteins (BMPs) belong to the Transforming Growth Factor-β (TGF-β) family. Initially identified due to their ability to induce bone formation, they are now known to have multiple functions in a variety of tissues, being critical not only during development for tissue morphogenesis and organogenesis but also during adult tissue homeostasis. This review focus on the liver as a target tissue for BMPs actions, devoting most efforts to summarize our knowledge on their recently recognized and/or e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 180 publications
(224 reference statements)
1
49
0
Order By: Relevance
“…The role of BMP9 in liver homeostasis is still unclear and controversial [10,11]. BMP9 was reported to be an autocrine/paracrine cytokine inhibiting adult (non-malignant) hepatocyte proliferation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The role of BMP9 in liver homeostasis is still unclear and controversial [10,11]. BMP9 was reported to be an autocrine/paracrine cytokine inhibiting adult (non-malignant) hepatocyte proliferation [3].…”
Section: Introductionmentioning
confidence: 99%
“…While the pivotal role of transforming growth factor beta (TGF-β) as a master cytokine controlling the progression of chronic liver disease is well established, 5 the implication of other TGF-β superfamily members such as the bone morphogenetic proteins (BMP) remains to be fully elucidated. 6 Of particular interest is BMP9, a member of this family that is primarily expressed in liver, and present in serum at bioactive concentration. 7,8 Our laboratory and others have shown that BMP9 promotes proliferation, survival and invasion in hepatocellular carcinoma cells, supporting a protumorigenic role of BMP9 in liver.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of stem-cell pluripotent genes is indicative of cellular reprogramming to a dedifferentiated state that occurs during HCC development [27]. BMP signaling has a complex role in regulating iron homeostasis, liver fibrosis, and liver regeneration [28]. TGF-β is known to induce transdifferentiation and production of collagen and extracellular matrix proteins in hepatic stellate cells, and deletion of the TGF-β receptor in hepatocytes has been shown to alleviate NASH [29].…”
Section: Discussionmentioning
confidence: 99%